2020
DOI: 10.1002/mds.28126
|View full text |Cite
|
Sign up to set email alerts
|

Skin Biopsy May Help to Distinguish Multiple System Atrophy–Parkinsonism from Parkinson's Disease With Orthostatic Hypotension

Abstract: Background The differential diagnosis between multiple system atrophy parkinsonism type (MSA‐P) and Parkinson's disease with orthostatic hypotension (PD+OH) is difficult because the 2 diseases have a similar clinical picture. The aim of this study is to distinguish MSA‐P from PD+OH by immunostaining for abnormal phosphorylated α‐synuclein at serine 129 (p‐syn) in cutaneous nerves. Method We recruited 50 patients with parkinsonism and chronic orthostatic hypotension: 25 patients fulfilled the diagnostic criteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
52
2
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(60 citation statements)
references
References 44 publications
(134 reference statements)
4
52
2
1
Order By: Relevance
“…The deposition morphology characteristics was identical to that of p-syn in the substantia nigra by autopsy ( 5 , 6 ). P-syn was found in synucleinopathies, such as PD, Lewy bodies (DLB), and multiple system atrophy (MSA), but not in normal controls and taupathies ( 7 12 ). These evidences indicated cutaneous p-syn could be a reliable peripheral biomarker for PD diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…The deposition morphology characteristics was identical to that of p-syn in the substantia nigra by autopsy ( 5 , 6 ). P-syn was found in synucleinopathies, such as PD, Lewy bodies (DLB), and multiple system atrophy (MSA), but not in normal controls and taupathies ( 7 12 ). These evidences indicated cutaneous p-syn could be a reliable peripheral biomarker for PD diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…The distribution pattern of p‐syn in PD in concern with biopsy sites had been published with controversy in recent years, indicating the heterozygous factors may influence the deposition. To our knowledge, two patterns had been reported, one was proximal‐distal gradient which was the main pattern reported by two groups, 9,10,26‐29 the other was homogenous pattern reported by Doppler in 2018 and another group in Switzerland 30,31 . Although a more distal distribution tendency was found in Doppler’s article, no significant difference was found between the distal and proximal sites (12/25 vs. 8/25).…”
Section: Discussionmentioning
confidence: 81%
“…PD patients with orthostatic hypotension (PD + OH) and without OH (PD‐OH) demonstrated both the above two distribution patterns recently, 28 suggesting sources of PD patients in concern with clinical profiles such as autonomic symptoms may also influence the p‐syn distribution pattern. The phenomenon was further supported by Donadio’s article in 2020, where all PD + OH patients displayed p‐syn deposits without a proximal–distal gradient 29 . Although the Doppler’s group and the Switzerland group reported a homogeneous p‐syn pattern, 30,31 none of the autonomic function especially OH was not clarified in the two articles.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…In addition to early diagnosis of PD, abnormally aggregated α-Syn in skin nerve fibers might also be used for differential diagnosis with other diseases. Donadio et al (2020) recently reported that the distribution difference of p-α-Syn in cutaneous nerves might help to distinguish MSA Parkinsonism type from PD with orthostatic hypotension. Wang et al also used RT-QuIC/PMCA and found that skin α-Syn had aggregation seeding activity that was significantly higher in individuals with PD and other synucleinopathies, compared with those with tauopathies and non-neurodegenerative controls (Wang Z. et al, 2020).…”
Section: The α-Syn Species In Rbcsmentioning
confidence: 99%